2014
DOI: 10.1108/jfm-04-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Research trend of joint ventures in construction: a two-decade taxonomic review

Abstract: Purpose -This paper aims to systematically and critically explore the research trend of construction joint ventures (CJVs) in some selected leading construction journals over the past two decades between 1993 and 2012. It is also expected that some valuable insights into the extended application of JVs to facilities service management and maintenance could be generated from the research findings.Design/methodology/approach -A powerful search engine "Scopus" was selected to identify those journals that have pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 54 publications
(135 reference statements)
3
75
0
Order By: Relevance
“…It is imperative for the agreement to be comprehensive and the fair setting out of the obligations, rights, risks and rewards for the partners (CIDB, 2004). This sentiment has been supported in the previous discourse of Hong et al, (2014); Kale et al, (2013); Hyun et al, (2013); Adnan et al, (2003) and Miller, (n.d.). Adnan et al, (2003) suggested that a good JV agreement is essential and can avoid a great deal of trouble and conflict in future JV operations.…”
Section: Comprehensive and Fair Written Agreementsupporting
confidence: 55%
See 1 more Smart Citation
“…It is imperative for the agreement to be comprehensive and the fair setting out of the obligations, rights, risks and rewards for the partners (CIDB, 2004). This sentiment has been supported in the previous discourse of Hong et al, (2014); Kale et al, (2013); Hyun et al, (2013); Adnan et al, (2003) and Miller, (n.d.). Adnan et al, (2003) suggested that a good JV agreement is essential and can avoid a great deal of trouble and conflict in future JV operations.…”
Section: Comprehensive and Fair Written Agreementsupporting
confidence: 55%
“…However, Manitshana (2012) study did not determine the influence of these CSFs to JV project success outcome in South Africa. Furthermore, Manitshana's (2012) CSFs differed from other researchers (Hong and Chan, 2014;Kale, Patil, Hiravennavar, and Kamane, 2013;Hyun and Ahn, 2013;Lambe, Spekman, and Hunt, 2011). Further, in a current study by Adnan et al, (2018) they identified seven (7) CSFs, which include inter-partner trust, criteria for partner selection, mutual understanding, agreement of contract, conflict, compatibility of objective, and management control.…”
Section: Introductionmentioning
confidence: 52%
“…Elsevier's Scopus has been used in similar reviews (e.g. Hong and Chan, 2014;Osei-Kyei and Chan, 2015) and it has a better accuracy and precision in performance than other search engines (such as Web of Science and Google Scholar) (Falagas et al, 2008). Tober (2011) also contended that Scopus is the best and most effective search engine for conducting a review of a topic.…”
Section: Methodsmentioning
confidence: 99%
“…The lists of publications were obtained by using a powerful search engine "Scopus" for a comprehensive search on the subject area. The Scopus search engine was chosen because it covers most publication databases in different research areas such as engineering, business, management, and accounting (Hong and Chan, 2014). Also, Scopus has been considered to perform better with respect to its accuracy and coverage than other search engines such as Web of Science, Google Scholar and PubMed (Falagas et al, 2008).…”
Section: Identifying Academic Journalsmentioning
confidence: 99%